PENGARUH KOMITMEN ORGANISASI, KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PERSONEL PADA SATUAN LALU LINTAS POLRES PAMEKASAN - jurnalmap map; Khairul Alam; Woro Utari; Subijanto ÔÇì (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT The purpose of this study is to find out how the two parties work both simultaneously organizational commitment, work ability and work motivation on the performance of personnel in the Pamekasan Police Resort of traffic unit. Respondents of this study were personnel of the Pamekasan Police Resort of traffic unit across 85 people. Using a sampling technique of 100 people. Analysis of the data used is multiple linear regression analysis. This type of research is experimental research, research uses quantitative research equipped with descriptive methods. The results showed organizational commitment, work motivation and simultaneous and significant work motivation on the performance of Pamekasan Police Precinct traffic unit personnel. Partially, the work ability has a positive and significant influence on the performance of the Pamekasan police traffic unit personnel, positive work motivation on the performance of Pamekasan police traffic unit personnel. Among the variables of organizational commitment and work ability, work motivation has a dominant performance on the personnel of the Pamekasan Police Resort of traffic unit. Keywords: organizational commitment, work ability, work motivation, personal performance